Embodied encounters: the self and suburbia in contemporary photography - Payne, Natalie Louise (My University, 2018)
The primary motivation of my research is to provide a theoretical framework for the production of my body of work Encountering Windrift, a series of autobiographical photographs focused on the domestic sphere of suburbia, familial relationships and the experience of mortality. In order to do so, I deploy a notion of embodiment. The idea of embodiment in art making has stimulated much discourse in recent years, questioning notions of subjectivity in relation to practice and reception. Applied specifically to certain modes of autobiographical photography, the theory of embodiment that I propose is based upon what I define as an ‘embodied encounter’ between the photographer and the photographed subject. In the photographs I analyse, the embodied encounter is engendered through the portrayal of everyday trauma such as failure, conflict, loss and grief. The embodied encounter is heightened by the apparent intimacy between photographer and subject, which I argue remains embodied in the resultant photograph. Maurice Merleau-Ponty’s notion of ‘the chiasm’ and Jill Bennett’s notion of ‘affective transaction’ serve to support my conception of the photograph as an embodied encounter in that both imply an intertwining of self and other. While the viewer may never be able to access another person’s subjective experience directly, I contend that certain formal and conceptual approaches to autobiographical photography may enable the viewer’s understanding of the photographer’s personal experience of space and history.
A dissertation submitted to the Faculty of Arts, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Fine Arts, 2018
Keywords: Motion in art; Ethnology in art; Technology and the arts